Analisis Kepuasan Pasien Pendaftaran Rawat Jalan Berbasis Rekam Medis Elektronik - Sartika Maulida Putri; Cut Husnul Khatimah; Julia Anita; Dara Alfi Syahrina (Pusat riset dan Inovasi Nasional, 2025)
Patient satisfaction is a feeling that arises from the performance of health services that have been obtained after the patient compares it with what was expected. Rather than the reality that occurs there are still complaints about outpatient registration services based on electronic medical records, Frequent obstacles are if the network is disrupted, then access to the EMR can be hampered or cannot be accessed at all and the limited capacity of the waiting room is also an obstacle, especially with the large number of patients during peak hours so that many patients wait outside the waiting room. This study aims to determine the level of patient satisfaction in outpatient registration based on EMR. This study uses a quantitative method with a population of 13,750 and a sample of 99 outpatients. Based on the results of the study in 2025, it can be concluded that patient satisfaction with RME-based outpatient registration in the aspect of tangibles can be categorized as